Agricultural drought impacts on crops sector and adaptation options in Mali: a macroeconomic computable general equilibrium analysis. (6th June 2019) - Montaud, Jean-Marc
Abstract: In Mali's current context, where the crops sector is particularly exposed and vulnerable to agricultural drought, this study assesses the economy-wide impacts of such events and the potential effectiveness of some adaptation strategies. Using a dynamic computable general equilibrium model, we conduct counterfactual simulations of various scenarios accounting for different levels of intensity and frequency of droughts over a 15-year period. We first show how mild, moderate and intense droughts currently experienced by the country affect its economic performance and considerably degrade the welfare of its households. We also show how these negative impacts could be aggravated in the future by the likely increased number of intense droughts threatened by global climate change. However, we finally show that there appears to be some room for Mali to maneuver in terms of drought-risk management policies, such as fostering the use of drought-tolerant crop varieties, improving drought early warning systems or extending irrigation capacities.